Dialogue systems for language learning: A meta-analysis - Bibauw, Serge; Van den Noortgate, Wim; François, Thomas; Desmet, Piet (Language learning & technology, 2022)
The present study offers a meta-analysis of effectiveness studies on dialogue-based CALL, systems affording a learner practice in a foreign language (L2) by interacting with a conversational agent (“bot”). Through a systematic inclusion and exclusion process, we identified 17 relevant meta-analyzable studies. We made use of Morris and DeShon’s (2002) formulas to compute comparable effect sizes across designs, including k = 100 individual effect sizes, which were analyzed through a multilevel random-effects model. Results confirm that dialogue-based CALL practice had a significant medium effect size on L2 proficiency development (d = 0.58). We performed extensive moderator analyses to explore the relative effectiveness on several learning outcomes of different types and features of dialogue-based CALL (type of interaction, modality, constraints, feedback, agent embodiment, gamification). Our study confirms the effectiveness of form-focused and goal-oriented systems, system-guided interactions, corrective feedback provision, and gamification features. Effects for lower proficiency learners, and on vocabulary, morphosyntax, holistic proficiency, and accuracy are established. Finally, we discuss expected evolutions in dialogue-based CALL and the language learning opportunities it offers.